The Volatility of Consumption in a Simple General Equilibrium Model - Tersman, Gunnar (IMF Working Papers; Working Paper ;, 1992)
This paper studies the volatility of consumption relative to output in the context of a simple general equilibrium model of a small open economy subject to exogenous shocks in productivity. With infinite horizons and exogenous relative prices, the model generates variance estimates that are well above what can be observed in empirical data. While finite horizons and endogenous terms of trade reduce the volatility of consumption, the model fails to generate sufficient serial correlation with respect to the consumption growth rate. If the household's decision problem is modified to take into account durability and adjustment costs, the model does well on both dimensions.